Petrology and mineralogy of the Ulaan Del Zr-Nb-REE deposit, Lake Zone, Western Mongolia - Oyunbat, Sanjsuren (Mongolian Geoscientist, 2020)
The Ulaan Del deposit is located in the Lake Zone, Western Mongolia. In the area, middle-late Devonian alkali dykes of the Khalzan Complex are hosted in the middle-late Cambrian granodiorite-tonalite of the Togthohiinshil Complex. The alkali dykes of the Khalzan complex comprise medium- to fine-grained syenite, microsyenite, syenite-porphyry and trachyte, trachyrhyolite, and trachyandesite. The dykes are replaced to silica, sericite, albite, fluorite and are brecciated. They crosscut by quartz and quartz-carbonate veinlets. The dykes contain zircon (>0.19% Zr) with a total of rare earth elements oxides >0.1%. The host rocks of the Togtokhiinshil complex are mid-K, metaluminous, I- type granite, depleted in HFSE. Based on geochemical and mineralogical data, economic REE mineralization is concentrated in syenite and syenite porphyry of calc-alkaline high K to shoshonite series of A- type granite, emplaced at within a plate setting. Syenite dykes are enriched in REE. Ore minerals are zircon, apatite, sphene, monazite, xenotime, synchysite, parisite, fluorite and REE complex minerals, pyrite, rutile and limonite. Magmatic, metasomatic and hydrothermal processes significantly contributed to the formation of Zr, Nb, REE and Y mineralization at the Ulaan Del deposit.